"Because Other People Have Done It": Coin-Trees and the Aesthetics of Imitation. (6th January 2016) - Houlbrook, Ceri
Abstract : This paper considers the centrality of imitation in relation to British coin-trees, which are exactly what their name suggests: trees which have been embedded with coins. In the eighteenth and nineteenth centuries, the custom of coin insertion was observed for folk-remedial purposes; depositors were hoping for cures to certain ailments through the process of "contagious transfer". However, the custom has experienced a recent resurgence, with many coin-trees dating to the 1990s, 2000s, and 2010s. The modern-day depositors of coins do not cite folk-remedies as the purpose behind their participation; instead, the majority refer to imitation as the primary motivating factor. Simply put, people insert coins into trees because they have witnessed other people doing so. The paper considers imitation as a dissemination mechanism of the coin-tree custom; as the process which not only ensures the continuation of the custom but also influences how it is observed. The aesthetics of imitation, for example, refers to the distributions of the actual coins within the coin-trees, which often follow neat geometric patterns, testifying to the depositors' inclination to maintain a broader design. This paper aims to demonstrate the central role of imitation in the "why" and "how" of participation in this contemporary custom, and to consider the broader archaeological implications of such a demonstration.